2010
DOI: 10.1002/ajmg.a.33332
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations in biliary atresia suggest region of potential disease susceptibility in 2q37.3

Abstract: Biliary atresia (BA) is a progressive, idiopathic obliteration of the extrahepatic biliary system occurring exclusively in the neonatal period. It is the most common disease leading to liver transplantation in children. The etiology of BA is unknown, although infectious, immune and genetic causes have been suggested. While the recurrence of BA in families is not common, there are more than 30 multiplex families reported and an underlying genetic susceptibility has been hypothesized. We screened a cohort of 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 40 publications
1
48
0
1
Order By: Relevance
“…Previously, we investigated potentially causative large genomic alterations in 35 patients compared with more than 2000 controls and uncovered overlapping deletions in 2q37.3 in the patients with BA. 19 In the current study, we extended this work to examine association with CNVs in 61 patients and 5088 healthy controls. This analysis uncovered a CNV region on chromosome 2 overlapping the previously identified region as well as additional regions (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we investigated potentially causative large genomic alterations in 35 patients compared with more than 2000 controls and uncovered overlapping deletions in 2q37.3 in the patients with BA. 19 In the current study, we extended this work to examine association with CNVs in 61 patients and 5088 healthy controls. This analysis uncovered a CNV region on chromosome 2 overlapping the previously identified region as well as additional regions (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…DNA was prepared from peripheral blood using standard extraction procedures. 19 The patients were genotyped on the Illumina Infinium II HumanHap 550 BeadChip SNP array (San Diego, CA) through the Center for Applied Genomics at CHOP. The Center for Applied Genomics also supplied genotypes of 5088 healthy controls run on the same platform.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many genetic studies, moreover, have recently reported. For example, genomic study including genome-wide association study identified a susceptibility locus for BA on 10q24.2 and 2q37.3 18 19. Moreover, DNA hypermethylation at the CD11a locus in CD4+ cells, polymorphisms of vascular endothelial growth factor gene, and two microRNAs (miR-29a/29b1) may contribute significantly to BA susceptibility, but polymorphisms of IL-4, IL-18, IFN-γ genes were unlikely 20–25.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The disease is most common in East Asia with a frequency of 1/5,000. 5 Reasons for this high incidence have not been described yet. Some analyses of time and space distribution of BA cases suggested seasonal variation and clustering of cases 6 , but these observations were not confirmed in larger studies.…”
Section: Epidemiologymentioning
confidence: 99%